Effects of Mitoquinone (MitoQ) Supplementation on Aerobic Exercise Performance and Oxidative Damage: A Systematic Review and Meta-analysis - Oliver Gonzalo-Skok; Rafael A. Casuso (SpringerOpen, 2024)
Abstract Background Contracting skeletal muscle produces reactive oxygen species (ROS) originating from both mitochondrial and cytosolic sources. The use of non-specific antioxidants, such as vitamins C and E, during exercise has produced inconsistent results in terms of exercise performance. Consequently, the effects of the mitochondrial-targeted coenzyme Q10, named Mitoquinone (MitoQ) on exercise responses are currently under investigation. Methods In this study, we conducted a meta-analysis to quantitatively synthesize research assessing the impact of MitoQ on aerobic endurance performance and exercise-induced oxidative damage. PubMed, Web of Science, and SCOPUS databases were used to select articles from inception to January 16th of 2024. Inclusion criteria were MitoQ supplementation must be compared with a placebo group, showing acute exercise responses in both; for crossover designs, at least 14 d of washout was needed, and exercise training can be concomitant to MitoQ or placebo supplementation if the study meets the other inclusion criteria points. The risk of bias was evaluated through the Critical Appraisal Checklist (JBI). Results We identified eight studies encompassing a total sample size of 188 subjects. Our findings indicate that MitoQ supplementation effectively reduces exercise-induced oxidative damage (SMD: -1.33; 95% CI: -2.24 to -0.43). Furthermore, our findings indicate that acute and/or chronic MitoQ supplementation does not improve endurance exercise performance (SMD: -0.50; 95% CI: -1.39 to 0.40) despite reducing exercise-induced oxidative stress. Notably, our sensitivity analysis reveals that MitoQ may benefit subjects with peripheral artery disease (PAD) in improving exercise tolerance. Conclusion While MitoQ effectively reduces exercise-induced oxidative damage, no evidence suggests that aerobic exercise performance is enhanced by either acute or chronic MitoQ supplementation. However, acute MitoQ supplementation may improve exercise tolerance in subjects with PAD. Future research should investigate whether MitoQ supplementation concurrent with exercise training (e.g., 4-16 weeks) alters adaptations induced by exercise alone and using different doses.